Mangrove Ecosystem sustainability Effort in Essential Ecosystem Areas (KEE) of Teluk Pangpang Banyuwangi Regency - Yanuar Yogha Pradana; Farida Pulansari; Rossyda Priyadarshini (Syntax Corporation Indonesia, 2023)
This study aims to determine priority alternative efforts in managing the mangrove ecosystem of KEE Teluk Pangpang Kab. banyuwangi. Process Hierarchy Analysis or AHP is used to determine priority alternatives in efforts to sustain mangrove ecosystems. A total of six (6) people who were expert informants were taken as respondents using purposive sampling consisting of community leaders, heads of Fishermen's groups, heads of Farmers' groups, Fisheries Service, and Academics. The results of the analysis show that for an alternative to violence, the mangrove ecosystem KEE Teluk Pangpang (Kedunggebang Village), Kab. banyuwangi, the main factor that must be considered is social (weight value = 0.689) with the most important aspect including involving community participation in the management of mangrove ecosystems (weight value = 0.701). Meanwhile it shows that alternative priority scales and efforts to sustain the mangrove ecosystem of KEE Teluk Pangpang (Kedunggebang Village) Kab. Banyuwangi with AHP, namely the order of priority is Ecotourism (weight value = 0.429), Silvofhisery (weight value = 0.377) and Traditional Fisheries (weight value = 0.194). Thus, alternative ecotourism efforts are a top priority in the sustainability of the mangrove ecosystem of KEE Teluk Pangpang (Kedunggebang Village) Kab. Banyuwangi. Ecotourism In terms of ecosystem sustainability, it is defined as an alternative tourism product that has the goal of developing sustainable tourism, namely tourism development that is ecologically feasible and ethically just and provides social benefits to the community.